2023
DOI: 10.1002/ajh.26806
|View full text |Cite|
|
Sign up to set email alerts
|

Thrombosis in multiple myeloma: Risk estimation by induction regimen and association with overall survival

Abstract: Lenalidomide‐containing (R) triplet and quadruplet regimens are the standard of care for multiple myeloma (MM) and have been shown to increase the risk of thrombosis. The association between thromboembolism (TE) and survival in the novel multidrug era is not yet delineated. In this study, we evaluated the incidence of TE during the first year of MM diagnosis, its association with the type of induction regimen, and its impact on overall survival. We studied 672 newly diagnosed MM (NDMM) patients who received a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The distinctive thrombogenicity of two induction regimens commonly used for NDMM — carfilzomib/Rd (KRd) and bortezomib/Rd (VRd) — has been a matter of debate, with the current literature revealing divergent findings. For instance, Piedra et al demonstrated an increased VTE incidence among KRd‐treated patients in comparison with VRd‐treated patients, whereas Gaballa et al found no significant difference in thrombosis rates between these triplets 11–16 . In view of the foregoing, we decided to perform a systematic review and meta‐analysis aimed at comparing the thromboembolic risk associated with KRD versus VRD as frontline therapy for NDMM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distinctive thrombogenicity of two induction regimens commonly used for NDMM — carfilzomib/Rd (KRd) and bortezomib/Rd (VRd) — has been a matter of debate, with the current literature revealing divergent findings. For instance, Piedra et al demonstrated an increased VTE incidence among KRd‐treated patients in comparison with VRd‐treated patients, whereas Gaballa et al found no significant difference in thrombosis rates between these triplets 11–16 . In view of the foregoing, we decided to perform a systematic review and meta‐analysis aimed at comparing the thromboembolic risk associated with KRD versus VRD as frontline therapy for NDMM.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Piedra et al demonstrated an increased VTE incidence among KRd-treated patients in comparison with VRd-treated patients, whereas Gaballa et al found no significant difference in thrombosis rates between these triplets. [11][12][13][14][15][16] In view of the foregoing, we decided to perform a systematic review and meta-analysis aimed at comparing the thromboembolic risk associated with KRD versus VRD as frontline therapy for NDMM.…”
mentioning
confidence: 99%
“…The combination of patient- (age and immobility) [ 2 ] and disease-specific (hypercoagulability, plasma viscosity, and endothelial inflammation) [ 3 ] risk factors and prothrombotic therapies (high dose dexamethasone and immunomodulatory drugs [IMiDs]) [ 4 ] increases thrombosis risk in a population perceived to be at high risk for bleeding. In the current era of novel triplet and quadruplet combinations and improved survival in MM, VTE still occurs in over 10% of patients, particularly in the first 6 months of treatment, and is associated with inferior survival [ 5 ].…”
Section: Introductionmentioning
confidence: 99%